Aprendizagem social de gestores de projeto - Pereira, Luciano dos Santos (2012)
Learning in a social means to engage in relations with other individuals, through a practice capable of powering the exchange of experience and knowledge in a reflective and conference about the learned. Unite the issues community of practice, strategy as practice and project management, consisted of a complex task, which define the limits determined to be necessary. The purpose of this study is to analyze how project managers social learn in project environments and how this learning affects the resolution of emerging problems in the projects. The study consists of qualitative research were interviewed eight project managers that work in enterprises linked to increased national shipowner (Petrobras). To collect data we used semistructured questionnaire with open questions for data analysis technique was used for content analysis. At the end of the study it was found that managers learn in social environments and projects that address emerging problems through knowledge from communities of practice.